2002
DOI: 10.1046/j.1365-2567.2002.01500.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in Lyme borreliosis: lack of early tumour necrosis factor‐α and transforming growth factor‐β1 responses are associated with chronic neuroborreliosis

Abstract: Summary The clinical outcome of the tick born infection Lyme borreliosis seems to be influenced by the type of immune response mounted during the disease, as suggested by various animal models. Here we report the serum and cerebrospinal fluid levels of tumour necrosis factor‐α (TNF‐α), transforming growth factor β1 (TGF‐β1) and interleukin‐6 (IL‐6) in samples drawn at different disease intervals during the course of non‐chronic neuroborreliosis (n=10), chronic neuroborreliosis (n=15), erythema migrans (n=8, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
25
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 33 publications
1
25
0
4
Order By: Relevance
“…High concentrations of interleukin 6 (IL-6), IL-8, IL-12, IL-18, gamma interferon (IFN-␥), and CXCL13 have been found in the CSF samples of patients suffering from Lyme neuroborreliosis (7)(8)(9)(10)(11). Interleukin 6 induces the final maturation of B cells into plasma cells, IL-8 is a chemotactic factor for immune cells, IL-12 induces the Th1 response, which results in a strong inflammatory reaction caused by IFN-␥ and tumor necrosis factor beta (TNF-␤), and IL-18 is an important regulator of the immune response, which in synergy with IL-12 increases the secretion of IFN-␥ (7,8).…”
mentioning
confidence: 99%
“…High concentrations of interleukin 6 (IL-6), IL-8, IL-12, IL-18, gamma interferon (IFN-␥), and CXCL13 have been found in the CSF samples of patients suffering from Lyme neuroborreliosis (7)(8)(9)(10)(11). Interleukin 6 induces the final maturation of B cells into plasma cells, IL-8 is a chemotactic factor for immune cells, IL-12 induces the Th1 response, which results in a strong inflammatory reaction caused by IFN-␥ and tumor necrosis factor beta (TNF-␤), and IL-18 is an important regulator of the immune response, which in synergy with IL-12 increases the secretion of IFN-␥ (7,8).…”
mentioning
confidence: 99%
“…Spirochetal persistence in the tissues has been associated with severe pathology (14,21,65) and both acute and chronic inflammatory conditions (50,59). Numerous studies have shown that B. burgdorferi and its lipoproteins can induce in a variety of cell types the release of proinflammatory cytokines, such as interleukin-1␣ (IL-1␣) (10), IL-1␤ (45), 23,45,54,55,64), IL-8 (10), IL-12 (30,45,58), tumor necrosis factor alpha (TNF-␣) (8,45,53,54,55,58,64), gamma interferon (IFN-␥) (22,23,24), IL-17 (35), granulocyte-macrophage colony-stimulating factor (GM-CSF) (67), and IL-18 (30). These cytokines may contribute to tissue inflammation and damage.…”
mentioning
confidence: 99%
“…В последние годы имеет место повышенный ин-терес к изучению функций цитокинов в формировании и регуляции защитно-приспособительных реакций орга-низма при инфекционных процессах [4][5][6]. Начальные фазы иммунного ответа на боррелиозную инфекцию протекают с высвобождением провоспалительных ци-токинов.…”
unclassified
“…Начальные фазы иммунного ответа на боррелиозную инфекцию протекают с высвобождением провоспалительных ци-токинов. Фазность цитокиновой регуляции проявляется закономерным компенсаторным увеличением продукции противовоспалительных цитокинов, способствующих купированию воспалительных процессов [4,7]. Актив-ность синтеза цитокинов, экспрессии рецепторов к ним на клетках-мишенях определяют характер течения за-болевания [6,7].…”
unclassified
See 1 more Smart Citation